Sistem Informasi Perpustakaan Sekolah Dasar Negeri 49 OKU Menggunakan Embarcadero XE2 Berbasis Client Server - Dhea; Sri Tita; Abdulloh (Universitas Mahakarya Asia, 2022)
From the observations and information obtained at the 49 OKU State Elementary School, they have not used the information system because they only use manual recording in inputting library data. So a design of the 49 OKU Talang Jawa State Elementary School Library Information system was made to make it easier to manage data. In this study, researchers used data collection methods, namely the observation method, the interview method and the library method. In making this system, system development tools are also used, namely Data Flow Diagrams (DFD), Context Diagrams, Entity Relationship Diagrams (ERD), as well as Embarcadero XE2 and PHP MyAdmin as databases. This research resulted in an information system designed to make it easier to manage library data. This application consists of several menus, namely: data input, process and search and reports.